Towards an improved flow rate estimation method - Bin Suffian, M.H. (EDP Sciences, 2014)
This paper presents the development of a technique for estimating flow rate. The intended application is to estimate the volume of oil spilled from a ruptured subsea pipeline, with improved accuracy over existing methods. In this work, two novel methods to estimate flow rate with high accuracy were considered. The first involves the use of 3D cameras to estimate volumetric flow rate and the other uses a 2D camera to estimate the flow velocity. Related works including 3D reconstruction, optical flow and the experimental setup are described. The 2D camera approach produced good results, with an error of 2 - 9. On the other hand, the use of 3D cameras needs further work, as the cameras are unable to detect the flow. Future work for this approach will be focused on overcoming this limitation and developing the method further. Â© 2014 Owned by the authors, published by EDP Sciences.